Uptake and efficacy of a systematic intensive smoking cessation intervention using motivational interviewing for smokers hospitalised for an acute coronary syndrome: a multicentre before–after study with parallel group comparisons. Issue 9 (20th September 2016) - Auer, Reto; Gencer, Baris; Tango, Rodrigo; Nanchen, David; Matter, Christian M; Lüscher, Thomas Felix; Windecker, Stephan; Mach, François; Cornuz, Jacques; Humair, Jean-Paul; Rodondi, Nicolas
Abstract : Objectives: To compare the efficacy of a proactive approach with a reactive approach to offer intensive smoking cessation intervention using motivational interviewing (MI). Design: Before–after comparison in 2 academic hospitals with parallel comparisons in 2 control hospitals. Setting: Academic hospitals in Switzerland. Participants: Smokers hospitalised for an acute coronary syndrome (ACS). Intervention: In the intervention hospitals during the intervention phase, a resident physician trained in MI systematically offered counselling to all smokers admitted for ACS, followed by 4 telephone counselling sessions over 2 months by a nurse trained in MI. In the observation phase, the in-hospital intervention was offered only to patients whose clinicians requested a smoking cessation intervention. In the control hospitals, no intensive smoking cessation intervention was offered. Primary and secondary outcomes: The primary outcome was 1 week smoking abstinence (point prevalence) at 12 months. Secondary outcomes were the number of smokers who received the in-hospital smoking cessation intervention and the duration of the intervention. Results: In the intervention centres during the intervention phase, 87% of smokers (N=193/225) received a smoking cessation intervention compared to 22% in the observational phase (p<0.001). Median duration of counselling was 50 min. During the intervention phase, 78% received a phone follow-up for a median total duration of 42 min in 4 sessions. Prescription of nicotine replacement therapy at discharge increased from 18% to 58% in the intervention phase (risk ratio (RR): 3.3 (95% CI 2.4 to 4.3; p≤0.001). Smoking cessation at 12-month increased from 43% to 51% comparing the observation and intervention phases (RR=1.20, 95% CI 0.98 to 1.46; p=0.08; 97% with outcome assessment). In the control hospitals, the RR for quitting was 1.02 (95% CI 0.84 to 1.25; p=0.8, 92% with outcome assessment). Conclusions: A proactive strategy offering intensive smoking cessation intervention based on MI to all smokers hospitalised for ACS significantly increases the uptake of smoking cessation counselling and might increase smoking abstinence at 12 months.